Influence of environmental integrity on the feeding biology of Astyanax altiparanae (Garutti & Britski, 2000) in the Ivinhema river basin - doi: 10.4025/actascibiolsci.v35i4.19497 - Viana, Lucilene Finoto; Suarez, Yzel Rondon; Lima-Junior, Sidnei Eduardo (Acta Scientiarum. Biological Sciences, 2013)
This study aimed at analyzing the influence of different levels of environmental integrity of streams of the Ivinhema river basin (Mato Grosso do Sul State, Brazil) on the diet of A. altiparanae. Samplings were performed from July 2001 to November 2011 at 101 sites, using sieves, seining and gill nets, and electrofishing. Streams were classified into three levels of environmental integrity. We analyzed 664 stomachs with the methods of frequency of occurrence and volumetric analysis index, combined in the Importance Index (AI). The species was omnivorous, with predominance of allochthonous resources. At the least impacted sites, the most representative resource was allochthonous plant material; and in the altered sites in the rainy period the most consumed item was allochthonous arthropods. On the other hand, at the most impacted sites in the dry period there was a lower consumption of allochthonous plant material and allochthonous arthropods, compared with other levels of environmental integrity considered, with higher consumption of autochthonous arthropods. The results evidenced that in the least impacted sites there was greater contribution from allochthonous resources, probably because these environments show a more preserved riparian forest.